Impact of Rural Microfinance on Small Farmers’ Participation in Agri-Food Value Chains in South Africa: A Systematic Review - Agholor, Azikiwe Isaac (Research on World Agricultural Economy, 2026)
The study addresses empirical evidence on the impact of rural microfinance on smallholder farmers’ participation in agri-food value chains in South Africa. The study objectives were to categorize evidence on how microfinance influences smallholder farmers’ integration into agri-food value chains and evaluate which financial services have the most significant effect on productivity and market participation. The study adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020, using the prescribed strategies to allow for transparency and replicability. The information sources encapsulate peer-reviewed journal articles, government reports, and grey literature. Procedurally, databases and numerous sources were searched as follows: Academic Databases, including Scopus, Web of Science, Science-Direct, EBSCOhost, SpringerLink; and regional sources such as African Journals Online (AJOL), Sabinet, Institutional Repositories which encompass the Food and Agriculture Organization of the United Nations (FAO), the International Fund for Agricultural Development (IFAD), World Bank, and the Department of Agriculture, Land Reform and Rural Development (DALRRD) reports; ResearchGate, Google Scholar, and Non-Governmental Organization (NGO) reports. The study reveals that access to microcredit and savings helps enhance smallholder participation in agri-food value chains by empowering investments in inputs, farm expansion, and productivity. For microfinance instruments, credit exhibited the strongest evidence of impact, facilitating market-oriented production and value chain integration. Savings groups significantly contribute to resilience and social capital, while insurance remains underutilized due to affordability and awareness constraints. Further, gender and socio-economic differences continue to mediate outcomes, necessitating tailored financial products and training programmes to ensure equitable participation. The study recommends improvement of micro-financial programme design, institutional partnerships, gender-responsive policies, and farmer education. ER